PENGARUH KUALITAS KEHIDUPAN KERJA DAN PARTISIPASI TERHADAP KEPUASAN KERJA PERAWAT RSUD BANGKINANG - Arna Ace; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of quality of work life and participation on the satisfaction of nurses work RSUD Bangkinang. Where two independent variables are proposed and one dependent variable, ie quality of work life and participation as independent variable and job satisfaction a ct as dependent variable.This research method is descriptive and quantitative by using program of SPSS 21, where sample used is nurse Non-PNS RSUD Bangkinang with responden counted 57 people. For sampling technique using census method. Techniques of data collection through questionnaires and interviews.The results of the analysis using validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test, and F test so that it can be seen that the quality of work life has a significant effect on job satisfaction, that participation has a significant effect on job satisfaction, and That quality of work life and participation have a significant effect on job satisfaction.Keywords: Quality of Work Life, Participation, and Job Satisfaction